2017
DOI: 10.1016/j.jceh.2017.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Characteristics of Hepatitis Delta Virus Infection in a Tertiary Hospital Setting in Cameroon

Abstract: The proportion of anti-HDV antibody positivity remains high in this setting and was significantly associated with more severe liver disease compared to those who were anti-HDV negative. More studies are needed to evaluate rates of HDV testing in other centers in Cameroon and the subregion. Preventive strategies for HBV prevention, which also apply to HDV, must still be reinforced by healthcare providers and policy makers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
9
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 26 publications
5
9
1
Order By: Relevance
“…It is similar to that found by Butler et al in 2018 [2] and Luma et al in 2017 [23]; this average age is the same as that found in HBV patients in Cameroon [24]. The male predominance found in this work is the same as that found by Stockdale et al in 2017 [25] in London and Luma et al in Cameroon in 2017 [23]. The risk factors found in delta virus infection are mainly male homosexuality, intravenous drug use, human immunodeficiency virus (HIV), hepatitis C virus infection and sexual intercourse with multiple partners [26,27].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…It is similar to that found by Butler et al in 2018 [2] and Luma et al in 2017 [23]; this average age is the same as that found in HBV patients in Cameroon [24]. The male predominance found in this work is the same as that found by Stockdale et al in 2017 [25] in London and Luma et al in Cameroon in 2017 [23]. The risk factors found in delta virus infection are mainly male homosexuality, intravenous drug use, human immunodeficiency virus (HIV), hepatitis C virus infection and sexual intercourse with multiple partners [26,27].…”
Section: Discussionsupporting
confidence: 92%
“…The mean age in our study was 36.33 ± 10.9 years. It is similar to that found by Butler et al in 2018 [2] and Luma et al in 2017 [23]; this average age is the same as that found in HBV patients in Cameroon [24]. The male predominance found in this work is the same as that found by Stockdale et al in 2017 [25] in London and Luma et al in Cameroon in 2017 [23].…”
Section: Discussionsupporting
confidence: 92%
“…In these settings, transmission of HDV through contact with the blood or other body fluids of an infected person is common ( 23 ), while the risk of vertical spread seems to be low ( 20 ). Recent data on the HDV seroprevalence among HBsAg carriers in Cameroon ranged from 11% ( 24 ) to 18% ( 25 ). HDV exhibits a high degree of genetic heterogeneity and has been classified into eight different clades (1 to 8) ( 26 ), of which clade 1 has a worldwide distribution ( 27 ).…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of anti-HDV in 258 cases of HBV-positive cases in Lebanon and Greece was 1.2% and 0.23% respectively. The prevalence of anti-HDV in HBsAg positive patients has been reported in Burkina Faso as 3.4%, in Libya as 2.5%, in California as 3.6%, and in Cameroon as 10.5% (28)(29)(30)(31). In general, studies have shown that the prevalence of HDV is declining around the world and this decline can be the result of global HBV vaccination, increased awareness, strategies for the importance of prevention and socioeconomic conditions (16).…”
Section: Discussionmentioning
confidence: 99%